Mengelola Kecerdasan Emosional dalam Pembelajaran Matematika - Kintoko Kintoko; Siti Suprihatiningsih; Triana Harmini (Ideas Publishing, 2023)
Teaching and learning activities in schools only emphasize students' academic results which prioritize cognitive abilities so that students are only used to memorizing formulas and do not know the understanding of the concept, while affective abilities have not been developed, one of which is emotional intelligence. This research aims to find out how to manage emotional intelligence in learning mathematics. The method used for this assessment is a literature study. Emotional intelligence must be instilled in students from an early age by healthily managing emotions, therefore learning mathematics is said to be successful if students have positive emotional intelligence. Emotional factors have a big influence on better learning outcomes in a lesson.